Application of ROC Criteria Prioritization Technique in Employee Performance Appraisal Evaluation - Widjaja, Warkianto; Suprihartini, Yayuk; Dirgantoro, Guruh Putro; W, Wahyudi (Yayasan Sraddha Panca Widya Nusantara, 2024)
Employee performance appraisal is very supportive in human resource management that affects various strategic decisions of the company, such as giving bonuses, benefits, and promotions. An objective and fair evaluation is needed to ensure that outstanding employees get the appreciation they deserve. This research aims to apply the Rank Order Centroid (ROC) technique in determining the priority of assessment criteria. Using 5 main criteria used are productivity, quality of work, discipline, initiative and creativity, and teamwork. The Rank Order Centroid (ROC) method is used because it is easy to determine the weight of the criteria based on the order of the main priorities that have been determined by the decision maker. From the final results of ranking 5 alternatives to the 3 best alternatives, it can be analyzed that the C1 criterion really determines the final score because it is the criteria with the highest priority so that it gets the greatest weight and can affect the assessment results. The implementation of this technique is expected to support more precise and objective decision making and can facilitate decision makers in determining the parameters of the assessment criteria obtained based on the level of priority order of criteria and criteria attributes.